Speech Acts by the Governor Candidates of North Sumatera in Political Debates - Vidya Dwi Amalia Zati; Sumarsih Sumarsih; Lince Sihombing (Universitas Negeri Medan, 2015)
The objectives of the research were to describe the types of speech acts used in televised political debates of governor candidates of North Sumatera, to derive the dominant type of speech acts used in televised political debates of governor candidates of North Sumatera and to elaborate the way of five governor candidates of North Sumatera use speech acts in televised political debates. This research was conducted by applying descriptive qualitative research. The findings show that there were only four types of speech acts used in televised political debates, Debat Pemilukada Sumatera Utara and Uji Publik Cagub dan Cawagub Sumatera Utara, they were assertives, directives, commissives and expressives. The dominant type of speech acts used in both televised political debates was assertives, with 82 utterances or 51.6% in Debat Pemilukada Sumatera Utara and 36 utterances or 41.37% in Uji Publik Cagub dan Cawagub Sumatera Utara. The way of governor candidates of North Sumatera used speech acts in televised political debates is in direct speech acts, they spoke straight to the point and clearly in order to make the other candidates and audiences understand their utterances. Keywords: Governor Candidate; Political Debate; Speech Acts